Discourse Analysis inside a Song - Espino Barranco, Verónica; Hernández Ángeles, Tomás (Edähi Boletín Científico de Ciencias Sociales y Humanidades del ICSHu, 2013)
This paper aims to show how discourse analysis is used to infer the context of an amazing song entitled “LDN”, which is composed by Lily Allen. It is essential to address the language in context because it can display social problems that occur in society, in this case, city life. The analysis is carried out by considering speech acts in order to discover: the social relation among the people, the context of the situation, the relation in the discourse and finally the composer’s attitudes, perceptions and beliefs about what can be seen in the city life of England. This paper is an example of how and when the language is used, discovered through discourse analysis.